The modulation of gut microbiota by herbal medicine to alleviate diabetic kidney disease – A review - Du, Jinxin; Yang, Meina; Zhang, Zhongwen; Cao, Baorui; Wang, Zhiying; Han, Jinxiang (Frontiers in Pharmacology, 2022)
Diabetic kidney disease (DKD), a severe complication of diabetes mellitus and a major cause of end-stage renal disease (ESRD), its treatment has been the key concern of the medical community. A large number of clinical studies have shown that herbal medicine can effectively retard the progression of DKD, although the mechanism by which this occurs is not fully understood. Recent studies have found that the development of DKD may be sped up by the dysbiosis of the gut microbiota and their metabolites. Herbal medicine has been reported to alleviate intestinal dysbiosis, promote the excretion of toxic metabolites, and reduce the secretion of uremic toxins. This might be a potential mechanism for herbal medicine to exert renal protective effects. However, current understanding of the modulation of the gut microbiota by herbal medicine to delay the progression of DKD is still insufficient. To our knowledge, there are no relevant reviews in this genre. Consequently, we reviewed the literature concerning the modulation effects of herbal medicine on gut microbiota in DKD.  In this review, we discussed the interaction between the gut and kidney in the case of DKD. We also discussed the potential mechanism by which the change of gut microbiota will promote the progression of DKD. Finally, the potential therapeutic interventions of herbal medicine and their extracts to slow down the progression of DKD by affecting the intestinal tracts were reviewed.